Restoration of Forests: Human Concern - Dadhich, Pragya; Jaiswal, Poonam (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Human depends upon the forest for their day-to-day need. The increasing population has caused the over-exploitation of natural forest resources. Initially, the rate of forest exploitation was balanced by the rate of natural restoration but in the last few centuries due to the population explosion and increased greed of humans, the rate of deforestation is far more than the rate of restoration, which results in the degradation of forests globally. Forest degradation is followed by many consequences including unavailability of forest goods and services, reduction in pollutant absorption by forests which in turn accelerate global warming, climate change, etc. There is an urgent need to conserve what we have left with and restore what we have lost otherwise the outcomes of human greed will be drastic. Forest restoration is the process of improving the health, productivity, and array of life of a forest and re-establishes the integrity of the ecosystem. There are usually 4 strategies of restoration used according to the type of ecosystem and level of degradation, these are rehabilitation, reconstruction, reclamation, and replacement. Principles involved in restoration are ecological (benefit the environment), economical (economically support the community), and community-based (enhance the community values like integrity, etc.). Restoration varies from site to site, according to the environment and species present in the degraded ecosystem, it is a normal belief that species with larger seed sizes can withstand stress conditions, and tree legumes form the excellent primary introduction subjects in such areas due to their nitrogen-fixing ability. The process of restoration involves multiple steps and for a successful restoration project implementation of each step should be careful. As with any other project, restoration has its challenges like fund availability, exotic species, lack of support and awareness, etc.